Spatial and Temporal Patterns in Housing Supply: A Descriptive Analysis - Ong, Rachel; Phelps, C.; Rowley, Steven; Wood, Gavin (Routledge, 2017)
© 2017 Editorial Board, Urban Policy and Research This paper provides an analysis of spatial and temporal patterns in housing supply in Australia over the period 2005–06 to 2015–16. It shows that by international standards, per capita housing supply is very strong in Australia. However, housing supply is concentrated in areas with relatively high prices. Over time, some changes in the geography of housing supply are emerging, including a closer match between the supply of units and “job-rich” locations. This paper concludes by discussing how understanding patterns of new supply can help policymakers determine interventions that increase housing supply’s impact to alleviate inflationary pressures, hence improving housing affordability.